A review of the impact of roadway vegetation on drivers' health and well-being and the risks associated with single-vehicle crashes. Issue 3 (3rd July 2017) - Van Treese II, Jeffery W.; Koeser, Andrew K.; Fitzpatrick, George E.; Olexa, Michael T.; Allen, Ethan J.
Abstract: Roadside trees can help calm traffic, define roadways and reduce drivers' stress. However, roadside trees are also one of the most common components of urban infrastructure involved in single-vehicle crashes. The aim of this review is to identify and summarise research findings on risk assessment for tree crashes and the effect of roadside vegetation on drivers' psychology and behaviour. The literature was obtained by entering keywords into multiple search engines and tracking down references that were cited in articles that were on-point. This literature review summarises findings from road safety research, identifying trends in tree and site factors that have been used to model single car crash frequency and severity. In looking at 10 similar studies, 8 found that the location of a tree (i.e. distance from the roadway) was a significant predictor of crash likelihood or severity. Other recurring predictors of tree-related car crashes include time of day and roadway geometry (e.g. the presence of a curve). In addition, this literature review summarises findings from road safety research regarding drivers' perception of trees in the streetscape and the impact that roadside vegetation has on drivers' behaviour and psychology. Generally, roadside vegetation had a positive psychological effect on drivers, in that it reduced drivers' stress and frustration, and was also correlated with reduced driving speeds.